How "Collective" Is Union Citizenship Behavior? Assessing Individual and Coworker Antecedents. (October 2014) - Snape, Ed; Redman, Tom; Gould-Williams, Julian
Contributing to an emerging literature on solidarity or group-norm effects on union participation, the authors examine the extent to which union citizenship behavior (UCB) can be characterized as a collective phenomenon. Findings from studies of UK local government workers and teachers suggest that, for organization-focused behaviors, it is meaningful to think of collective or group-level UCB. Furthermore, group-level UCB had a significant positive association with individual-level UCB. There was no evidence that a greater consistency of citizenship within a unit was associated with a stronger relationship between collective and individual citizenship behaviors. These findings suggest that it is worthwhile to analyze UCB as a collective phenomenon, and the authors call for more work on the contextual antecedents of union citizenship and participation.